Cadmium effects on growth and development as well as reproduction of Boettcherisca peregrine in the parental generation and first filial generation - WU Guo-xing; YE Gong-yin; HU Cui; CHENG Jia-an (浙江大学学报. 农业与生命科学版, 2006)
The survival, growth and development as well as reproduction of Boettcherisca peregrina (Diptera: Sarcophagidae) in the parental generation were significantly influenced as newly oviposited larvae were exposed to various concentration of Cd2+ administered in the artificial diet until pupation. With increasing of Cd2+ concentration, the weight of larvae, pupae and adults become lighter, the length of larvae and pupae turned shorter, the percentages of pupation, emergence, mating and the fecundity were reduced, the duration of larvae and pupae were prolonged, and the life span of adults were shortened. However, cadmium effect on the sex ratio was not marked. In contrast, the survival, growth and development as well as reproduction of B. peregrine in the first filial generation unexposed to Cd2+ were almost not markedly affected in spite of the fact that their parental generation had previously been exposed to Cd2+. Thus, it is clear that cadmium effects on the parental generation of this fly cannot be transferred to its next generation. In addition, change in Cd2+ content of the fly during metamorphosis both in the parental generation and the first filial generation were also determined.